KfW/ZEW CO2 Barometer 2016 - Carbon Edition. How the EU ETS can contribute to meeting the ambitious targets of the Paris Agreement - Daniel Osberghaus; Peter Heindl; Katrin Sommerfeld; Holger Höfling (KfW Bankengruppe und Zentrum für Europäische Wirtschaftsforschung (ZEW), 2016)
The KfW/ZEW CO2 Barometer - developed as part of a cooperation project of KfW Bankengruppe and the Centre for European Economic Research (ZEW) - has been analysing the situation of the German companies regulated under the European Union Emissions Trading System (EU ETS) on an annual basis since 2009. The study's objective is to closely monitor firm behaviour in carbon markets in order to provide detailed information for policy-makers, businesses, and the research community. For that purpose, all German firms regulated under the EU ETS are invited to participate in the survey every year. On average, approximately 130 companies of 800 have responded to the questionnaire per year. The results are reported in an annual publication, the KfW/ZEW CO2 Barometer - Carbon Edition. Important findings of this year's survey: - While the Paris Agreement has the potential to be a major breakthrough in global climate negotiations, a majority of German companies participating in the EU ETS do not expect that it will be effective in reducing global emissions, not even in the long run. - In the current trading period the EU ETS has generated only weak incentives for firms to implement carbon abatement measures. - The trading scheme should be further strengthened to ensure the effectiveness and efficiency of climate action in Europe. – – Im Rahmen eines Kooperationsprojekts mit der KfW Bankengruppe führt das Zentrum für Europäische Wirtschaftsforschung (ZEW) seit 2009 jährlich eine Befragung unter allen durch das Europäische Emissionshandelssystem (EU-EHS) regulierten Unternehmen in Deutschland durch. Die Erhebung liefert Daten zur Analyse der Auswirkungen des EU-EHS auf die regulierten Unternehmen in Deutschland. Dazu werden jährlich rund 800 Unternehmen kontaktiert, von denen im Durchschnitt ungefähr 130 Unternehmen Auskunft über ihre aktuelle Situation und zukünftige Strategien geben. Die Ergebnisse werden jedes Jahr in einem breit angelegten Marktreport, dem KfW/ZEW-CO2-Barometer - Carbon Edition, veröffentlicht. Das Wichtigste in Kürze: - Obwohl das Pariser Klimaschutzabkommen ein wichtiger Durchbruch in den globalen Klimaverhandlungen sein kann, erwartet die Mehrheit der befragten deutschen Unternehmen keine Reduzierung der globalen Treibhausgasemissionen - auch nicht in der langen Frist. - In der derzeitigen Handelsperiode hat das EU-Emissionshandelssystem nur geringe Anreize zur Emissionsreduzierung gesetzt. - Der Emissionshandel sollte weiter gestärkt werden, um die Wirksamkeit und Effizienz der europäischen Klimapolitik zu fördern.
Keywords: 330